EXPEDIENCY OF MARKERS FOR EARLY DETECTION OF ACUTE KIDNEY INJURY SEQUELAE TO TYPE 2 DIABETES MELLITUS - MuniLakshmi u; Kn, Shashidhar; C, Muninarayana; Reddy, Madhavi; V, Lakshmaiah (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Estimation of Cystatin C (Cys C), traditional markers, inflammatory, and endothelial cell activation markers can identify subjects who are at increased risk for future acute kidney injury (AKI) after diabetes. Methods: A total of 210 subjects, having 70 subjects in each group between the age group of 45-75 years were enrolled in our study. Results: Body mass index (BMI), obesity index, waist circumference, and waist–hip ratio higher in Group III and Group II compared to Group I with a significant p<0.001. All the biochemical parameters were significantly higher in Group III compared to Group I and Group II with a narrow difference between Group III and Group II. Serum Cys C was significantly correlated with creatinine and NO. Whereas serum creatinine (SCr) shows strong positive correlation with BMI, fasting blood sugar, HbA1c, NO, and high-sensitivity C-reactive protein. Estimated glomerular filtration rate (eGFR) and triglycerides show inverse relation to creatinine with a significant p-value. The serum Cys C showed an area under the curve (AUC) of 0.950 with a cutoff value of 1.06, SCr with an AUC of 0.617, and eGFR with AUC of 0.588. Conclusion: Elevated levels of biomarker Cys C, SCr, and albumin-creatinine ratio are predictors of AKI in the setting of diabetes. Baseline inflammatory and endothelial activation markers may also be useful for predicting future risk of AKI in diabetes mellitus. Hopefully, the advent of new biomarkers will help defining the kidney at risk rather than relying simply on creatinine. To date, none of the new AKI biomarkers have undergone a similar rigorous assessment, but the current progress will hopefully lead to success and ultimately to improvement in patient outcome. Keywords: Type 2 diabetes mellitus, Acute kidney injury, Biomarkers, Inflammation, Endothelium.